Extracting knowledge from english translated quran using NLP pattern - Rohana, Ismail; Zainab, Abu Bakar; Nurazzah, Abd Rahman (Penerbit UTM Press, 2015)
Ontology is able to represent knowledge from an abstract view into formal semantics. It is essential for the success of knowledge-based systems because it has been used to share vocabulary, discover new knowledge, flexible access of knowledge and easy integration of knowledge. Currently, Ontology from Quran is not complete and most of the development is done manually. Manual development of ontology is time consuming and labor intensive task. Hence, the automatic or semi-automatic ontology development which is a field of Ontology Learning is needed to efficiently extract knowledge and transform it into Ontology. Current techniques employed in Ontology Learning are based on statistical and Natural Language Processing.This paper provides result from an experiment to extract knowledge usingthe existing Natural Language Processing (NLP) Pattern based on the Ontology Learning approach. Initial experiment shows that the pattern could be used to extract knowledge in terms of relations that exist in English translated Quran. In addition, NLP could also use to identify new pattern that can be further explored.